Volume regulation in Mycoplasma gallisepticum: evidence that Na+ is extruded via a primary Na+ pump. - Shirvan, M H (1989)
The primary extrusion of Na+ from Mycoplasma gallisepticum cells was demonstrated by showing that when Na+-loaded cells were incubated with both glucose (10 mM) and the uncoupler SF6847 (0.4 microM), rapid acidification of the cell interior occurred, resulting in the quenching of acridine orange fluorescence. No acidification was obtained with Na+-depleted cells or with cells loaded with either KCl, RbCl, LiCl, or CsCl. Acidification was inhibited by dicyclohexylcarbodiimide (50 microM) and diethylstilbesterol (50 microM), but not by vanadate (100 microM). By collapsing delta chi with tetraphenylphosphonium (200 microM) or KCl (25 mM), the fluorescence was dequenched. The results are consistent with a delta chi-driven uncoupler-dependent proton gradient generated by an electrogenic ion pump specific for Na+. The ATPase activity of M. gallisepticum membranes was found to be Mg2+ dependent over the entire pH range tested (5.5 to 9.5). Na+ (greater than 10 mM) caused a threefold increase in the ATPase activity at pH 8.5, but had only a small effect at pH 5.5. In an Na+-free medium, the enzyme exhibited a pH optimum of 7.0 to 7.5, with a specific activity of 30 +/- 5 mumol of phosphate released per h per mg of membrane protein. In the presence of Na+, the optimum pH was between 8.5 and 9.0, with a specific activity of 52 +/- 6 mumol. The Na+-stimulated ATPase activity at pH 8.5 was much more stable to prolonged storage than the Na+-independent activity. Further evidence that two distinct ATPases exist was obtained by showing that M. gallisepticum membranes possess a 52-kilodalton (kDa) protein that reacts with antibodies raised against the beta-subunit of Escherichia coli ATPase as well as a 68-kDa protein that reacts with the anti-yeast plasma membrane ATPases antibodies. It is postulated that the Na+ -stimulated ATPases functions as the electrogenic Na+ pump.